Dendritic cell generation and CD4+CD25HIGHFOXP3+ regulatory T cells in human head and neck carcinoma during radio-chemotherapy - Schuler, Patrick; Börger, V.; Bölke, E.; Habermehl, Daniel; Matuschek, C.; Wild, C. A.; Greve, J.; Bas, M.; Schilling, B.; Bergmann, C.; Trellakis, S.; Budach, W.; et al. (European journal of medical research, 2011)
Regulatory T cells (Treg) and dendritic cells (DC) play an important role in tumor immunity and immune escape. However, their interplay and the effects of anti-cancer therapy on the human immune system are largely unknown.
Im Titel sind die Pluszeichen und HIGH hochgestellt
Gesehen am 27.10.2022